Since you have the equation the radius is found like this....
Since the radius of a circle of is distance from the center of a circle to the outside of the circle the radius can be found by finding the distance between (2,5) and (-1,4)....
There is a formula for this....
The square root of the following quantiy:
[(x1 - x2)^2 + (y1 - y2)^2]
An ordered recall is (x,y)
The subscripts on x an y tell you which ordered pair the x or y value comes from. For example:
(2,5) = (x1, y1)
This makes x1 = 2 and y1 = 5
(-1,4) = (x2, y2)
This makes x2 = -1 and y2 = 4
Returning to our equation:
The square root of the following quantiy:
[(x1 - x2)^2 + (y1 - y2)^2]
Substitute x1, x2, y1, and y2:
You get the following:
The square root of the following quantiy:
[(2 - (-1))^2 + (5 - 4)^2]
If you simplify further you get:
The square root of the following quantiy:
[(3)^2 + (1)^2]
Simplifty further by getting squaring 3 and 1
The square root of the following quantiy:
[9 + 1]
Simplifty further by adding 9 and 1
The square root of the following quantiy:
[10]
Now if you take the square root of 10 you get
3.16227766
Therefore the radius is the square root of ten or 3.16227766
By the way in the equation of a circle r needs to be sqaured Giving the the final equation of:
(x-2)^2+(y-5)^2=r^2
or....
(x-2)^2+(y-5)^2=10
Note: Since sqaure a number undoes the sqaure root this is why r^2 = 10
2007-01-06 10:57:15
·
answer #1
·
answered by googooslide2000 3
·
1⤊
1⤋
First: take (-1, 4) and place the numbers in the given formula >
(-1 - 2)^2 + (4 - 5)^2 = r
(-3)^2 + (-1)^2 = r
9 + 1 = r
10 = r
r = 10
r = V`10
(*V` represents the radical sign/square root)
2007-01-06 20:29:28
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
Actually, its: (x-2)²+(y-5)²=r²;
your (x,y) is (-1,4), plugging in gives you:
(-1-2)²+(4-5)²=r²;
9+1=r²;
r=â(10)
2007-01-06 18:37:56
·
answer #3
·
answered by Esse Est Percipi 4
·
1⤊
0⤋
So far so good, except I think it's supposed to equal r-squared. You might want to check that.
You'd need to use the distance formula with the two points you have to find the length of the radius
d = sqrt( (y2-y1)^2 + (x2-x1)^2 )
2007-01-06 18:41:19
·
answer #4
·
answered by hunneebee22 4
·
0⤊
0⤋
(-1 - 2)^2 + (4 - 5)^2 = r^2
(-3)^2 + (-1)^2 = r^2
9 + 1 = r^2
10 = r^2
(x - 2)^2 + (y - 5)^2 = 10
Radius = sqrt(10)
2007-01-06 22:46:21
·
answer #5
·
answered by Sherman81 6
·
0⤊
0⤋
The equation is this:
(x-2)^2+(y-5)^2=r^2
Radius formula:
r=â(x2-x1)^2+(y2-y1)^2
r=â(-1-2)^2+(4-5)^2
r=â(-3)^2+(-1)^2
r=â9+1
r=â10
2007-01-06 19:03:08
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋